Robotic process automation and the work identity of accountants - Minogue, Charlotte (My University, 2019)
Advances in technology create change, dilemmas and great possibilities for companies and their finance function. The accounting field is continuously evolving, as technology based tools are able to mimic the work and actions of humans. Robotic process automation (RPA) is the most recent automation technology to transform financial accounting by providing a quick, accurate and effective way to perform routine financial accounting tasks. These disruptive changes can cause various reactions in financial accountants ranging from positive to negative. Thus, identity theory, which includes work identity, provides a way to better understand RPA and its effects from the human per-spective. The objective of this thesis was to discover the relationship between RPA and the work identity of accountants. More closely, the point was to find out the effects that RPA has on the work identity and roles of accountants in addition to discover which aspects of RPA strengthen or threaten the work identity of accountants. Moreover, the aim was to see how accountants perceive future automation and their future roles and work opportunities in financial accounting. The empirical data of this qualitative research was collected through semi-structured interviews with eight financial accountants from one case company with various educational backgrounds, financial accounting experience as well as knowledge and use of RPA. After data collection the interviews were analysed using discourse analysis. The findings of the study showed that there are various effects that RPA has on the roles and work identity of accountants, which mostly depends on the use and knowledge of RPA. Mostly RPA was perceived well with RPA bringing beneficial changes to the work of accountants. The increased job satisfaction and better quality work impacted work identity positively while the possibility of losing a job and malfunction had a negative impact on work identity. Furthermore, the future of financial accounting was seen with increased automation either RPA or artificial intelligence and the roles of accountants were predicted to be different in the future.
Keywords: robotic process automation, work identity, financial accounting, artificial Intelligence